Three doses of BNT162b2 COVID-19 mRNA vaccine establish long-lasting CD8+ T cell immunity in CLL and MDS patients - Hernandez, Susana Patricia Amaya; Hersby, Ditte Stampe; Munk, Kamilla Kjærgaard; Tamhane, Tripti; Trubach, Darya; Tagliamonte, Maria; Buonaguro, Luigi; Gang, Anne Ortved; Hadrup, Sine Reker; Saini, Sunil Kumar (Frontiers in Immunology, 2023)
Patients with hematological malignancies are prioritized for COVID-19 vaccine due to their high risk for severe SARS-CoV-2 infection-related disease and mortality. To understand T cell immunity, its long-term persistence, and its correlation with antibody response, we evaluated the BNT162b2 COVID-19 mRNA vaccine-specific immune response in chronic lymphocytic leukemia (CLL) and myeloid dysplastic syndrome (MDS) patients. Longitudinal analysis of CD8+ T cells using DNA-barcoded peptide-MHC multimers covering the full SARS-CoV-2 Spike-protein (415 peptides) showed vaccine-specific T cell activation and persistence of memory T cells up to six months post-vaccination. Surprisingly, a higher frequency of vaccine-induced antigen-specific CD8+ T cells was observed in the patient group compared to a healthy donor group. Furthermore, and importantly, immunization with the second booster dose significantly increased the frequency of antigen-specific CD8+ T cells as well as the total number of T cell specificities. Altogether 59 BNT162b2 mRNA vaccine-derived immunogenic responses were identified, of which 23 established long-term CD8+ T cell memory response with a strong immunodominance for NYNYLYRLF (HLA-A24:02) and YLQPRTFLL (HLA-A02:01) epitopes. In summary, we mapped the vaccine-induced antigen-specific CD8+ T cells and showed a booster-specific activation and enrichment of memory T cells that could be important for long-term disease protection in this patient group.